Body Worn Cameras, Procedural Justice, and Police Legitimacy: A Controlled Experimental Evaluation of Traffic Stops. (2nd January 2020) - Demir, Mustafa; Apel, Robert; Braga, Anthony A.; Brunson, Rod K.; Ariel, Barak
Abstract: Police legitimacy is generally regarded as a view among community members that police departments play an appropriate role in implementing rules governing public conduct. Placing body worn cameras (BWCs) on police officers has been suggested as a potentially important response to police legitimacy crises. We use a rigorous controlled quasi-experimental evaluation to test the impact of BWCs on citizen perceptions of procedural justice and police legitimacy during traffic stops in Turkey. Relative to stops by officers without BWCs, we find that motorists stopped by officers with BWCs reported improved perceptions of procedural justice in the encounter and perceptions of legitimacy of traffic officers and the police more generally. Supplementary analyses suggest that the perceived improvements in police legitimacy were entirely driven by perceived enhancements in procedural justice during the traffic stop encounter. These findings suggest that body camera technology help ensure procedurally just encounters and improve public perceptions of police legitimacy.